A Genealogy of Moderate Islam: Governmentality and Discourses of Islam in Indonesia’s Foreign Policy - Umar, Ahmad Rizky Mardhatillah (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2016)
This article analyses the political construction of ‘Moderate Islam Discourse’ in contemporary Indonesian Foreign Policy. Since 2004, the Indonesian Ministry of Foreign Affairs has campaigned for ‘Moderate Islam’ as the main image of Indonesian Islam. Within this discourse, Islam is conceived as ‘moderate’ and ‘tolerant’ as well as inherently compatible with democracy. However, in a more critical perspective, ‘Moderate Islam’’ also contains a political and discursive construction. By using a genealogical approach, I argue that the articulation Islam in Indonesia’s foreign policy is influenced by the ideological underpinnings of each political regime as well as the hegemonic discourse operating in international politics. Furthermore, I argue that there have been three discourses of Islam in Indonesia’s foreign policy, as articulated by different political regimes, namely (1) Islam as religious identity; (2) Moderate Islam from below; and (3) Moderate Islam as a part of the Global War on Terror project.DOI: 10.15408/sdi.v23i3.3157